St. Jerome, an Unknown XVIth Century Flemish Painting: Iconography and Affiliation - Piquer Garzón, Alfredo (Eikón / Imago, 2017)
XIXth. Century Historiography revealed a series of paintings whose topic is St. Jerome within the symbolic context of the vanitas, all of them originated in Flemish Renaissance. This series seem to respond to the same iconographic model, which has given rise to an enormous number of variants, although no specific affiliation has been established between them, nor a possible initial model. This article presents a 16th Century Flemish table that could be the iconographic pattern of the families of known copies of the subject, considering its coming to Spain in the second half of the same century and through the analysis of criticism which has so far located the origins of the abovementioned series in the Durero’s San Jerónimo (Museum of Ancient Art in Lisbon).